Natural Variation in Volatile Emissions of the Invasive Weed Calluna vulgaris in New Zealand - Evans Effah; D. Paul Barrett; Paul G. Peterson; A. Jonathan R. Godfrey; Murray A. Potter; Jarmo K. Holopainen; Andrea Clavijo McCormick (Plants, 2020)
Invasive plants pose a threat to natural ecosystems, changing the community composition and ecological dynamics. One aspect that has received little attention is the production and emission of volatile organic compounds (VOCs) by invasive plants. Investigating VOCs is important because they are involved in vital ecological interactions such as pollination, herbivory and plant competition. Heather, Calluna vulgaris, is a major invasive weed in New Zealand, especially on the Central Plateau, where it has spread rapidly since its introduction in 1912, outcompeting native species. However, the chemical behaviour of heather in its invaded ranges is poorly understood. We aimed to explore the natural variation in volatile emissions of heather and the biotic and abiotic factors influencing them on the Central Plateau of New Zealand. To this end, foliar volatiles produced by heather at four different sites were collected and analysed using gas chromatography coupled to mass spectrometry. Soil properties, herbivory and other environmental data were also collected at each site to investigate their effects on VOC emissions using generalised linear models (GLMs). Our results reveal significant differences in VOC emissions between sites and suggest that soil nutrients are the main factor accounting for these differences. Herbivory and temperature had only a minor effect, while soil water content had no impact. Further studies are needed to investigate how these variations in the invasive plant’s foliar volatiles influence native species.